The Collaboration between the Lecturer’s Community Service and Student’s Community Service for Disaster-Resilient in Pondok Aren District, South Tangerang, Indonesia - Yahya Darmawan; Novvria Sagita; Suharni Suharni; Sandy Tri Gustono (Universitas Lambung Mangkurat, 2022)
This study investigated the effectiveness of the collaboration program between the Lecturer's Community Service (PKM) and Student's Community Service (KKN) of the State College of Meteorology Climatology and Geophysics (STMKG) for disaster-resilient in Pondok Aren District, South Tangerang, Indonesia. Community participatory methods have been applied during this program which elaborates the role of lecturers, students and the community in enhancing the disaster awareness community. Some activities have been done during this program, such as providing the spatial information maps, designing the earthquake's evacuation route, planting the bio pure absorption hole technology (LRB), installing the Automatic Rain Gauge (ARG), counselling to school and Forum Group Discussion (FGD). As the result, Pondok Aren district appreciated STMKG, which has chosen their office as the target of program. The improving knowledge about the disaster vulnerability in Pondok Aren district has formed during the program which the pre- and post-questioners of FGD can evaluate. The collaboration-community service program proved more effective in activities, funding and time consumption than the conventional program. Furthermore, the causes of floods disaster in the Pondok Aren district also can be listed during this program.